State Policy of Innovative Development of National Economy: Situation and Issues of Implementation - PARYZKYY, Igor V. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018, 2019)
The creation and introduction of innovation is the basis of technological, socio-economic and environmental development of society, and the success of innovative economic transformations and the possibility of its exit from the crisis depends on the state innovation policy. Therefore, it is important to analyze the real state and problems of implementing state innovation policy in accordance with the declared key principles of innovation activity and strategic priorities of innovative development of Ukraine. The methodological basis of the article is the general scientific methods of scientific research: induction and deduction, comparative analysis and synthesis, generalization and realization of results, as well as historical method. The state of development and utilization of national scientific, technical and innovative potential in accordance with the place of Ukraine in the ranking of world indices, which assess the level of innovative economy of the country, is investigated, and the unsatisfactory level of innovative changes in the national economy is determined. The effectiveness of the state innovation policy from the perspective of financial support of innovation activity has been analyzed, and it has been revealed that the main reason for inefficient state policy of innovation development is lack of financial support and irrational use of budgetary funds by main entities of research and innovation activities in Ukraine. The main problems of implementation of the state policy of innovative development of the national economy have been identified, the steps for increasing its efficiency and effectiveness were proposed.